Carbon nanotube and composite for RF application and electronic packaging - Siah, Chun Fei (Nanyang Technological University, 2022)
The outstanding properties of carbon nanotubes (CNTs) have led to their being studied by nanomaterials researchers worldwide. A major focus of these studies is the development of device prototypes based on CNTs. However, the integration of CNTs into consumer products is limited by several challenges, the greatest of which is CNT synthesis. Specifically, current syntheses require temperatures greater than 600℃ to obtain sufficiently crystalline CNT products, but these harsh conditions can also cause reflow of metallisation layers, which has adverse effects on component and device functioning. In addition, mismatched coefficients of heat expansion of different materials in chips can result in the development of high stresses during the manufacture of CNT-based devices, which can ultimately cause device failure. To address these limitations, this thesis described research on the separation of CNT synthesis from device fabrication. This involved the printing of CNTs onto a target (device) substrate or the transfer of CNTs from a sacrificial (growth) substrate to a target (device) substrate. CNTs were grown from carbon precursors in an argon-hydrogen carrier-gas mixture via thermal chemical vapour deposition. A layer of low-melting-point tin–silver–copper (SAC) solder was deposited onto the as-grown CNTs, a flip-chip bonder was used to attach the resulting solder-coated CNTs to designated locations on target substrates, and then eutectic bonding was performed. Cooling of the solder-bonded interfaces followed by a release process separated the sacrificial and target substrates, completing the CNT transfer process. CNT transfer can also be performed via thermocompression bonding. Two binder materials were explored for this purpose, namely gold (Au) and copper (Cu), and both were found to be suitable for transferring CNTs. The electrical properties of CNTs transferred from different binder materials were characterised. The potential applications of CNT transfer were demonstrated by incorporating it into the design and fabrication of several devices, which were fully characterised. First, a VACNT-based air-filled substrate integrated waveguide for the transmission of electromagnetic waves at greater than 50 GHz was designed using high-frequency simulation software with a developed CNT model. The waveguide devices were bonded with SAC, Au and Cu before S-parameter characterization. They exhibited a maximum transmission loss of approximately -10 dB, which is the highest loss achieved till date for a VACNT-based waveguide. Additionally, a CNT pi-bridge structure was fabricated to study the electrical resistance of bonded interfaces. This revealed that the Au binder exhibited negligible resistance, and that the overall resistance of the structure was linearly dependent on the length of the CNTs. In conclusion, this thesis described efficient methods for the transfer of CNTs that can be performed using one of three different binders. This means that a binder can be chosen to suit the process used for the fabrication of a CNT-containing device or component, and its intended application.